The Implementation of Fishbowl Strategy in Teaching Speaking Explanation to the Eleventh Grade Students at English Course - Supriyanto Supriyanto; Dinna Merris Maya Sari; Yuliyanto Sabat (P-SEMART JOURNAL, 2022)
Speaking is one of language skills that are able to used by students in teaching learning process. The teacher also used fishbowl strategy in teaching speaking explanation in which students are able to share their idea and opinion in this strategy. The purpose of the research was to describe the implementation of fishbowl strategy in teaching speaking explanation to the eleventh grade students at English course and to describe students’ responses in teaching speaking by using fishbowl strategy. The research was descriptive qualitative with the data collected from filed note observation, check list observation, questionnaire, and interview. The finding of the implementation of fishbowl strategy in teaching speaking explanation to eleventh grade students at English course was the teacher gave warming up, explained explanation text, made two groups, asked students to turn and talk their opinion and idea, got discussion started, told others students to listen carefully. When the small group finished, asked students to make comment on discussion in the first meeting and the second meeting. In students’ responses by using fishbowl strategy, the percentage showed the answer YES 92,7% and NO 7,3%. It was inferred that fishbowl strategy was able to help the students more active, communicative, and confident in speaking English. The students should be critical thinking in speaking explanation text, and the teacher should remind students to be more enthusiastic.